Learning from the South American Feminist Resistance: the Struggle against Globalized Capitalism - Navarro Ruiz, Clara (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
Within the last years, we are witnessing a process of negotiation of diverse Free-Trade and Investment Agreements (FTAs) which seem to threaten our fundamental rights. In the next lines we tackle this process and its possible risks. Following to that, and thanks to Amaia Perez Orozco’s texts, we analyze some of the possible resistance strategies against them. The experience of South American feminists related to the ALCA Free-Trade Agreement, suspended in 2005, are the core of her argumentation.
Keywords: FTAs; Feminist Economics; South America.